METHODOLOGY FOR CONDUCTING PHYSICAL EDUCATION FOR 6-7-YEAR-OLD SCHOOL CHILDREN - Romanova Lola Karimbaevna (Web of Journals Publishing, 2025)
This article discusses the methodology for conducting physical education classes for 6-7-year-old schoolchildren.
Keywords: Physical ability, competition method, demonstration method, oral method, figurative story, oral instruction, health-improving tasks, educational task, movement skills, educational task.